The Myth of Post-Reform Income Stagnation : Evidence from Brazil and Mexico - de Carvalho Filho, Irineu; Chamon, Marcos (Washington, D.C. : International Monetary Fund, 2008)
Economic policies are often judged by a handful of statistics, some of which may be biased during periods of change. We estimate the income growth implied by the evolution of food demand and durable good ownership in post-reform Brazil and Mexico, and find that changes in consumption patterns are inconsistent with official estimates of near stagnant incomes. That is attributed to biases in the price deflator. The estimated unmeasured income gains are higher for poorer households, implying marked reductions in "real" inequality. These findings challenge the conventional wisdom that post-reform income growth was low and did not benefit the poor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet